Calcium Ions Signaling: Targets for Attack and Utilization by Viruses - Qu, Yang; Sun, Yingjie; Yang, Zengqi; Ding, Chan (Frontiers in Microbiology, 2022)
Calcium, as a second intracellular messenger, participate in various physiological and biochemical processes, including cell growth and proliferation, energy metabolism, information transfer, cell death, and immune response. Ca2+ channels or pumps in plasma and organelle membranes and Ca2+-related proteins maintain Ca2+ homeostasis by regulating Ca2+ inflow, outflow and buffering to avoid any adverse effects caused by Ca2+ overload or depletion. Thus, Ca2+ signaling also provides a target for virus invasion, replication, proliferation and release. After hijacking the host cell, viruses exploit Ca2+ signaling to regulate apoptosis and resist host immunity to establish persistent infection. In this review, we discuss cellular Ca2+ signaling and channels, interaction of calcium-associated proteins with viruses, and host cell fate, as well as the role of Ca2+ in cell death and antiviral response during viral infection.